Amino Acid-Dependent Alterations in Cell Wall and Cell Morphology of Deinococcus indicus DR1 - Chauhan, Deepika; Srivastava, Pulkit Anupam; Ritzl, Barbara; Yennamalli, Ragothaman M.; Cava, Felipe; Priyadarshini, Richa (Frontiers in Microbiology, 2019)
Deinococcus radiodurans exhibits growth medium-dependent morphological variation in cell shape, but there is no evidence whether this phenomenon is observed in other members of the Deinococcaceae family. In this study, we isolated a red-pigmented, aerobic, Deinococcus indicus strain DR1 from Dadri wetland, India. This D. indicus strain exhibited cell–morphology transition from rod-shaped cells to multi-cell chains in a growth-medium-dependent fashion. In response to addition of 1% casamino acids in the minimal growth medium, rod-shaped cells formed multi-cell chains. Addition of all 20 amino acids to the minimal medium was able to recapitulate the phenotype. Specifically, a combination of L-methionine, L-lysine, L-aspartate, and L-threonine caused morphological alterations. The transition from rod shape to multi-cell chains is due to delay in daughter cell separation after cell division. Minimal medium supplemented with L-ornithine alone was able to cause cell morphology changes. Furthermore, a comparative UPLC analysis of PG fragments isolated from D. indicus cells propagated in different growth media revealed alterations in the PG composition. An increase in the overall cross-linkage of PG was observed in muropeptides from nutrient-rich TSB and NB media versus PYE medium. Overall our study highlights that environmental conditions influence PG composition and cell morphology in D. indicus.